Dammarane-type triterpene oligoglycosides from the leaves and stems of Panax notoginseng and their antiinflammatory activities - Li, Juan (J Ginseng Res, 2019)
BACKGROUND: Inflammation is widespread in the clinical pathology and closely associated to the progress of many diseases. Triterpenoid saponins as a key group of active ingredients in Panax notoginseng (Burk.) F.H. Chen were demonstrated to show antiinflammatory effects. However, the chemical structures of saponins in the leaves and stems of Panax notoginseng (PNLS) are still not fully clear. Herein, the isolation, purification and further evaluation of the antiinflammatory activity of dammarane-type triterpenoid saponins from PNLS were conducted. METHODS: Silica gel and reversed-phase C8 column chromatography were used. Furthermore, preparative HPLC was used as a final purification technique to obtain minor saponins with high purities. MS, NMR experiments, and chemical methods were used in the structural identifications. The antiinflammatory activities of the isolated saponins were assessed by measuring the nitric oxide production in RAW 264.7 cells stimulated by lipopolysaccharides. Real-time reverse transcription polymerase chain reaction was used to measure the gene expressions of inflammation-related gene. RESULTS: Eight new minor dammarane-type triterpene oligoglycosides, namely notoginsenosides LK1-LK8 (1–8) were obtained from PNLS, along with seven known ones. Among the isolated saponins, gypenoside IX significantly suppressed the nitric oxide production and inflammatory cytokines including tumor necrosis factor-α, interleukin 10, interferon-inducible protein 10 and interleukin-1β. CONCLUSION: The eight saponins may enrich and expand the chemical library of saponins in Panax genus. Moreover, it is reported for the first time that gypenoside IX showed moderate antiinflammatory activity.